Análise da relação entre a satisfação dos consumidores e os preços ofertados no sítio booking.com - Borges, Igor Roberto (Universidade do Vale do Rio dos Sinos, 2013)
Many papers reveal evidence of influence of evaluations and critical analyzes posted online on demand, however do not correlate the prices charged. Starting from this gap, the present research examines whether the customer satisfaction originated from the online assessments is or is not associated with the prices offered by hotels rentals of their rooms. Nevertheless, search to verify if the variable satisfaction should or should not be included as input variable in mathematical models that seek to maximize revenue per available rooms in hotels. For both, a quantitative survey was conducted with 5,459 cases based on 499 hotels in 25 different countries. Online assessments recorded on the website booking.com were analyzed in order to relate them to the price charged by hotels for rent rooms. The results indicate that the different quality attributes of services, available on the website researched, should not be included in models to maximize revenues. The exception is the availability of rooms, available on the website, which has recommended its inclusion. The indication is based on the findings of this research, which confirm that hotels who practice higher prices, end up having more rooms available, as well the otherwise. However, hotels that charge higher rates can increase their revenues more than the others.
Keywords: Satisfaction and hotels; Social media; Price; Satisfação e hotéis; Mídias sociais; Preço; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação